Treatment of bilateral mammary ptosis and pectus excavatum through the same incision in one surgical stage - Rocha, Fernando Passos; Pires, Jefferson André; Torres, Vinicius Franchini; Fagundes, Djalma José (São Paulo Medical Journal, 2012)
CONTEXT: Congenital deformities of the anterior thoracic wall are characterized by unusual development of the costal cartilages. All these medical conditions are frequently associated with a variety of breast deformities. Several surgical techniques have been described for correcting them, going from sternochondroplasty to, nowadays, minimally invasive techniques and silicone prosthesis implantation. CASE REPORT: The present article reports the case of a young female patient who presented bilateral mammary ptosis and moderate pectus excavatum that caused a protrusion between the eighth and the tenth ribs and consequent esthetic disharmony. The proposed surgical treatment included not only subglandular breast implants of polyurethane, but also resection of part of the rib cartilage and a bone segment from the eighth, ninth and tenth ribs by means of a single submammary incision in order to make the scar minimally visible. Correction through a single incision benefited the patient and provided an excellent esthetic result. CONCLUSIONS: The techniques used to repair bilateral mammary ptosis and pectus excavatum by plastic and thoracic surgery teams, respectively, have been shown to be efficient for correcting both deformities. An excellent esthetic and functional result was obtained, with consequent reestablishment of the patient’s self-esteem.